Miskonsepsi Siswa dalam Menyelesaikan Masalah Pecahan berdasarkan Tingkat Keyakinan Siswa - Febyanti, Adinda Isna; Sukoriyanto, Sukoriyanto (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2024)
This study aims to describe students’ misconceptions in solving fraction problems based on their level of belief. The research method employed is qualitative, with a descriptive research approach. Subjects were selected students who experienced misconceptions in solving problems. The results of examining students’ answers showed that out of 27 students, 18 did not know the concept, and 9 had misconceptions. Selected 5 students who experienced misconceptions as subjects to ensure data variation due to similarities in the answers or responses given. The misconceptions made by the subjects include: 1) Generalization misconception occurred because the subjects made mistakes in explaining the meaning of numerator and denominator of fractions and mistakes in applying the concept of addition and substructions of fractions; 2) Calculation misconception occurred because the subject made mistakes in calculating fractions and mistakes in simplifying fractions; 3) Notation misconception occurred because the subject made mistakes in using operation symbols and mistakes in writing numbers; 4) Language misconception occurred because the subject made mistakes in converting information into mathematical language. To overcome this problem, teachers are advised to provide a deeper conceptual understanding and practice problems regularly to improve students' understanding.